Developing interpersonal problem solving in the elementary school - Borges, Dâmaris Simon Camelo; Marturano, Edna Maria (Paidéia (Ribeirão Preto), 2002)
An inverse relationship between interpersonal problem solving abilities and inhibited or impulsive behaviors has been demonstrated. Taking into account the frequently reported disciplinary problems in classrooms, this study examined the efficacy of the "I Can Problem Solve" curriculum for the development of these abilities. Fifty-five first-grade students in an elementary public school participated. Two groups were formed: intervention group (n=31) and comparison group (n=24). The children who participated in the program improved their ability for generation of alternative solutions for interpersonal problems as compared to their colleagues who did not participate in the program. Students who initially engaged the most in interpersonal conflicts reduced their participation in these events.